Synergistic effect of CD47 blockade in combination with cordycepin treatment against cancer - Chen Feng; Chen Feng; Chen Feng; Rongzhang Chen; Rongzhang Chen; Rongzhang Chen; Weiwei Fang; Weiwei Fang; Weiwei Fang; Xinran Gao; Xinran Gao; Xinran Gao; et al. (Frontiers Media S.A., 2023)
Cordycepin is widely considered a direct tumor-suppressive agent. However, few studies have investigated as the effect of cordycepin therapy on the tumor microenvironment (TME). In our present study, we demonstrated that cordycepin could weaken the function of M1-like macrophages in the TME and also contribute to macrophage polarization toward the M2 phenotype. Herein, we established a combined therapeutic strategy combining cordycepin and an anti-CD47 antibody. By using single-cell RNA sequencing (scRNA-seq), we showed that the combination treatment could significantly enhance the effect of cordycepin, which would reactivate macrophages and reverse macrophage polarization. In addition, the combination treatment could regulate the proportion of CD8+ T cells to prolong the progression-free survival (PFS) of patients with digestive tract malignancies. Finally, flow cytometry validated the changes in the proportions of tumor-associated macrophages (TAMs) and tumor-infiltrating lymphocytes (TILs). Collectively, our findings suggested that the combination treatment of cordycepin and the anti-CD47 antibody could significantly enhance tumor suppression, increase the proportion of M1 macrophages, and decrease the proportion of M2 macrophages. In addition, the PFS in patients with digestive tract malignancies would be prolonged by regulating CD8+ T cells.